Thermomechanical properties of 3D-printed sand moulds using inorganic binder - Jochen Wendling; Jesper Thorborg; Marcel Sterzenbach; Johannes Schüssler; Andreas Bührig-Polaczek (Heliyon, 2023)
Additive Manufacturing of 3D-printed sand cores using the binder jetting process is well-established in prototype manufacturing. Due to the rising focus on sustainability and the fact that printed cores are shifting to serial production, a transition from organic to inorganic binder systems is taking place. To ensure a stable casting process and reduce the scrap rate accurate simulation tools are required. However, a study about the thermomechanical properties and the anisotropy of 3D-printed sand cores has not yet been conducted. In this work the thermomechanical properties of 3D-printed sand cores in three different printing orientations using inorganic binder are given. In contrast to homogeneous materials like metals, the simulation of sand cores requires new material models due to the dependency to hydrostatic pressure. The Drucker-Prager soil plasticity model is used, and the parameters needed for the Drucker-Prager-Cap model until 500°C are analysed using the three-point-bending test, the indirect tensile test and the uniaxial compression test. In addition to these specific parameters, also general parameters required for mechanical simulation like the Young's modulus, the Poisson's ratio, the density and the thermal expansion coefficient are given. In comparison to the reference binder system for shot cores using inorganic binder, the 3D-printed cores showed a higher mechanical strength. In the tensile region due to the higher binder content and in the compressive region due to the higher AFS number. Furthermore, the binder system for printed cores showed a lower thermostability.